2011
DOI: 10.5536/kjps.2011.38.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Pine Needle Powder on Meat Quality and Physico-chemical Properties of Chicken Meat

Abstract: This study were carried to investigate to the effects of diet supplemented with pine needle powder on pH, total phenol contents, DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity, TBARS (thiobarbituric acid reactive substance), WHC (water holding capacity), shear force, sensory evaluation, meat color, and fatty acid composition of chicken meat. Broiler chicks were fed the corresponding diets containing 0% pine needle powder (Control), 0.3% pine needle powder (T1), 0.6% pine needle powder (T2), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…In an experiment, higher DPPH-radical scavenging activity in the thigh meat of broilers was observed in 1 and 2% PNP supplemental groups as compared to the control group (Kim et al, 2012 ). Similar results were obtained by Park and Kim ( 2011 ) regarding DPPH-radical scavenging activity in the thigh meat of broilers supplemented with 0.3, 0.6, and 0.9% PNP. The present study showed no significant effect of PNP supplementation on DPPH activity of breast meat.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In an experiment, higher DPPH-radical scavenging activity in the thigh meat of broilers was observed in 1 and 2% PNP supplemental groups as compared to the control group (Kim et al, 2012 ). Similar results were obtained by Park and Kim ( 2011 ) regarding DPPH-radical scavenging activity in the thigh meat of broilers supplemented with 0.3, 0.6, and 0.9% PNP. The present study showed no significant effect of PNP supplementation on DPPH activity of breast meat.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed that supplementation of PNP decreased the pH of breast meat samples (1-D storage at 4°C); however, no change in pH was observed for meats stored up to 10 D. Kim et al ( 2012 ) also reported a significant decrease in pH of thigh meat of broilers when supplemented with PNP (1 and 2%), and this decrease was explained by the presence of bioactive compounds in the meat especially polyphenols and flavonoids from the PNP. Park and Kim ( 2011 ) also observed similar results for pH of thigh meat when broiler diets were supplemented with 0.3, 0.6, and 0.9% PNP. In their experiment, supplementing broiler diets with 0.6 and 0.9% PNP had resulted in a significant decrease in pH of thigh meat as compared to the control and 0.3% supplemental group.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations